(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Zivzik pomegranate is an important source of income for producers in Siirt province. There are many harmful insect species that cause loss of yield and quality in pomegranate. This study was carried out to determine the pest insect species in Zivzik pomegranate production areas in Siirt province and its districts in 2018 and 2019. The study was conducted total in 38 orchards in 12 villages in 3 districts (Central, Şirvan and Pervari). To determine the insect species, samples were collected with pheromone trap, shoot cutting, visual inspection, Japanese umbrella and cultivation methods. As a result of the studies, a total of 24 harmful insect species belonging to 7 orders and 19 families were identified. Among these species, Carob moth (Ectomyelois ceratoniae (Zeller, 1839)), Pomegranate aphid (Aphis punicae Passerini, 1863) and Chrysobothris affinis (Fabricius, 1794) were found to be important species. dried fruit beetle (Carpophilus spp.) fruit fly (Drosophila melanogaster Meigen, 1830), Ash whitefly (Siphoninus phillyreae (Haliday, 1835)), leopard moth borer (Zeuzera pyrina Linnaeus, 1761) and Tenuipalpus granati Sayed, 1946 were determined as secondary pests. Furthermore, Chrysobothris affinis (Fabricius, 1794) detected in this study is the first record for the pomegranate fauna of Turkey